(untitled) (Modern Problems of Metallurgy, 2019)
Drum loaders that are used on sintering machines for loading of charge on a grate from furnace-bars does not provide the receipt of rational segregation of charge on the height of layer. Attempts to bring down negative influence of the segregation of material got here by piling on the grate of sintering machines two or the more layers of charge did not give the expected results. A question of achievement of the set distribution of material of charge on largeness on the height of layer due to the guided segregation of the loaded material still is an actual scientific and practical task. The analysis of efficiency of the known methods and facilities of forming of layer of charge is executed at her piling on the furnace-bar grate of sintering machines. It is shown that one of the most perspective directions of forming of layer of charge is a management by the process of segregation of granular charge on the height of layer depending on her largeness and maintenance in it fuels. For the division of charge there can one of types of technological equipment be linear delimiters on factious composition. Realization of the offered flow sheets with the use of linear delimiters provides the set distribution of factions of granular charge on the height of layer with the gradual height of maintenance of fuel in the epiphyses of charge, what the productivity of sintering machines allows to increase and to improve quality of the produced agglomerate.